Credit default swaps, the leverage effect, and cross-sectional predictability of equity and firm asset volatility - Forte, Santiago; Lovreta, Lidija (Journal of Corporate Finance, 2023)
Leverage represents both a fundamental component of equity volatility and a long-run selection variable. Based on this premise, we investigate the influence of leverage on the long-run cross-sectional predictability of future realized equity volatility. Leverage makes equity volatility significantly less predictable than underlying firm asset volatility, a result that is robust to different predictors of future realized volatility: credit default swap implied, historical, and option implied volatility. A simple model of optimal capital structure, wherein companies maximize tax benefits subject to a common maximum default probability (minimum credit rating) target, helps explain this finding.